Real effects of Quantitative Easing at the Zero-Lower Bound: Structural VAR-based evidence from Japan - Sebastian Watzka; Heike Schenkelberg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Using monthly post-1995 Japanese data we propose a new sign-restriction based approach to identify monetary policy shocks when the economy is at the zero-lower bound (ZLB). The identifying restrictions are thoroughly grounded in liquidity trap theory. Our results show that a quantitative easing shock leads to a significant but temporary rise in industrial production. The effect on the price level is significantly positive and permanent. Inflation does therefore temporarily rise but returns to zero subsequently. In addition, we show the shock has even stronger effects on these variables if stock prices react positively. Our results are robust to different specifications, in particular to the further identification of aggregate demand and supply shocks under liquidity trap conditions. Accordingly, our results imply that while the Japanese Quantitative Easing experiment was successful in stimulating economic activity and inflation in the shortrun, it did not lead to any permanent increase in the inflation rate. We believe these results are interesting not only for the Japanese economy, but also for other advanced economies where monetary policy is currently constrained by the ZLB.
Keywords: E52; E51; E58; 330